The Quaternary Geologic History of the Canadian Rocky Mountains - Bobrowsky, Peter; Rutter, Nathaniel (Géographie physique et Quaternaire, 1992)
ABSTRACTThe Canadian Rocky Mountains figured prominently during the glacial history of western Canada. First as a western limit or boundary to the Laurentide Ice Sheet, second as an eastern margin of the Cordilleran Ice Sheet, and finally as a centre of local Montane ice. Throughout the Quaternary, complex interactions of glacier ice from these three ice sources markedly changed the physical form of the Rocky Mountains, Trench and Foothills areas. Investigations into the Quaternary history of this region have been ongoing since the beginning of the last century. Since about 1950, the number of studies performed in this area have increased significantly. This paper briefly reviews the historical accomplishments of Quaternary work in the region up to the period of about 1950. From this time to the present, individual study efforts are examined in detail according to the three geographic regions: 1) the northern Rocky Mountains (from the Liard Plateau south to the McGregor Plateau), 2) the central Rocky Mountains (from the McGregor Plateau south to the Porcupine Hills) and 3) the southern Rocky Mountains (from the Porcupine Hills south to the international border). In the northern region, geologic data suggest a maximum of two Rocky Mountain glaciations and only one Laurentide glaciation and no ice coalescence. In the central region, three of four Rocky Mountain events, and at least two Laurentide events are known. Only in the central region is there good evidence for ice coalescence, but the timing of this event is not clearly established. In the south, at least three Rocky Mountain episodes and a variable number of Laurentide episodes are recognized. There is no evidence for ice coalescence. A number of facts support the proposal that Cordilleran ice crossed the Continental Divide and joined with local Montane ice at several locations. However, this expansion of western ice occurred before the Late Wisconsinan in all areas but Jasper. In general, the chronological data presented suggest that the Late Wisconsinan glaciation in the Rocky Mountains was a short-lived event which started around or after 20 ka years ago and ended before 12 ka ago.